Multitargeted Platinum(IV) Anticancer Complexes Bearing Pyridinyl Ligands as Axial Leaving Groups. (27th March 2023) - Zhou, Qiyuan; Chen, Shu; Xu, Zoufeng; Liu, Gongyuan; Zhang, Shuyuan; Wang, Zhigang; Tse, Man‐Kit; Yiu, Shek‐Man; Zhu, Guangyu
Abstract: Although multitargeted Pt IV anticancer prodrugs have shown significant activities in reducing drug resistance, the types of bioactive ligands and drugs that can be conjugated to the Pt center remain limited to O‐donors. Herein, we report the synthesis of Pt IV complexes bearing axial pyridines via ligand exchange reactions. Unexpectedly, the axial pyridines are quickly released after reduction, indicating their potential to be utilized as axial leaving groups. We further expand our synthetic approach to obtaining two multitargeted Pt IV prodrugs containing bioactive pyridinyl ligands: a PARP inhibitor and an EGFR tyrosine kinase inhibitor; these conjugates exhibit great potential for overcoming drug resistance, and the latter conjugate inhibits the growth of Pt‐resistant tumor in vivo. This research adds to the array of synthetic methods for accessing Pt IV prodrugs and significantly increases the types of bioactive axial ligands that can be conjugated to a Pt IV center. Abstract : Novel pyridinyl Pt IV complexes obtained by ligand exchange reactions could quickly be reduced to the Pt II parent drugs. The axial pyridines acted as leaving group ligands and were utilized for designing multitargeted anticancer prodrugs. These multitargeted pyridinyl Pt IV complexes were effective in killing Pt‐resistant cancer cells and inhibiting tumor growth.